Multicontrast MRI Quantification of Focal Inflammation and Degeneration in Multiple Sclerosis. (29th July 2015) - Bonnier, Guillaume; Roche, Alexis; Romascano, David; Simioni, Samanta; Meskaldji, Djalel Eddine; Rotzinger, David; Lin, Ying-Chia; Menegaz, Gloria; Schluep, Myriam; Du Pasquier, Renaud; Sumpf, Tilman Johannes; Frahm, Jens; et al.
Abstract : Introduction . Local microstructural pathology in multiple sclerosis patients might influence their clinical performance. This study applied multicontrast MRI to quantify inflammation and neurodegeneration in MS lesions. We explored the impact of MRI-based lesion pathology in cognition and disability. Methods . 36 relapsing-remitting MS subjects and 18 healthy controls underwent neurological, cognitive, behavioural examinations and 3 T MRI including (i) fluid attenuated inversion recovery, double inversion recovery, and magnetization-prepared gradient echo for lesion count; (ii) T1, T2, and T2 * relaxometry and magnetisation transfer imaging for lesion tissue characterization. Lesions were classified according to the extent of inflammation/neurodegeneration. A generalized linear model assessed the contribution of lesion groups to clinical performances. Results . Four lesion groups were identified and characterized by (1) absence of significant alterations, (2) prevalent inflammation, (3) concomitant inflammation and microdegeneration, and (4) prevalent tissue loss. Groups 1, 3, 4 correlated with general disability (Adj-R 2 = 0.6 ; P = 0.0005 ), executive function (Adj-R 2 = 0.5 ; P = 0.004 ), verbal memory (Adj-R 2 = 0.4 ; P = 0.02 ), and attention (Adj-R 2 = 0.5 ; P = 0.002 ). Conclusion . Multicontrast MRI provides a new approach to infer in vivo histopathology of plaques. Our results support evidence that neurodegeneration is the major determinant of patients' disability and cognitive dysfunction.